KAJIAN CONCRETE, REPRESENTATIONAL, ABSTRACT (CRA) DALAM PEMBELAJARAN MATEMATIKA - Mochamad Ayi Lutfi; Hepsi Nindiasari; Etika Khaerunisa (Program Studi Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2026)
This research is motivated by the widespread study of Concrete Representational Abstract (CRA) in mathematics learning across various focuses, levels, and methods. The purpose of this study is to examine the trend of CRA research and identify the dominant focus, distribution of educational levels, research methods, contribution of findings, and research gaps. The method used is a Systematic Literature Review (SLR) with the PRISMA flow through the stages of identification, screening, eligibility, and inclusion. Articles were searched through Google Scholar, DOAJ, Sinta, Scopus, ERIC, and ScienceDirect in the period 2017–2026. Of the 28 identified articles, 21 articles met the inclusion criteria and were analyzed based on year, method, level, study focus, instruments, main results, and limitations. The results of the study indicate that CRA research mostly focuses on conceptual understanding and is dominated by quantitative methods. CRA studies have also developed towards mathematical representation, mathematical literacy, knowledge retention, creative problem solving, inclusive learning, and media integration. These findings indicate that CRA contributes as an instructional framework that helps students’ understanding transition from concrete to abstract, but cannot yet be generalized because a meta-analysis has not been conducted.